Action, culture and metaphor: finding common ground in research on public language use. (January 2016) - Fowler, Carol A.; Hodges, Bert H.
Abstract: The papers in this issue offer valuable perspectives on public language activities as they are embedded in cultural and social contexts. The perspectives are diverse in their theoretical underpinnings, their domains of study, and their methodologies, but they share concerns about action and interaction, learning and the relation of language and culture. They represent language studies from the perspective of the distributed language approach, ecological psychology, dynamical systems, and others. Topics included are: theoretical tools and insights (from Aristotle, Bakhtin, Clark, Harris, Shannon, Rescorla) that should be valuable for research on public, embodied, interpersonal language use; studies of negotiation networks as a way to study development of common ground; and metaphor as an everyday use of language that children discover and use early in their lives. Methodologies include theoretical analysis, experimental research, and case studies. They illustrate some of the important issues and challenges facing research and theory on public, between person language use, and offer some promising possibilities.